PENGARUH E-MONEY DAN ALAT PEMBAYARAN MENGGUNAKAN KARTU (APMK) TERHADAP JUMLAH UANG BEREDAR (M1) PERIODE 2013-2019 - Yeslika, Aritonang Br; Anthony, Mayes; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to determine the effect of E-money and Card-Based Payment Instruments (APMK) against the supply money in Indonesia period 2013-2019. The data used in this research is time series data from 2013 to 2019, obtained from Bank Indonesia (BI). The independent variables in this study is emoney (X1), credit cards (X2) and debit cards (X3), while the dependent variable is the supply money (Y). This research uses a quantitative method, and uses multiple linear analysis models with the help of the SPSS 24 computer program (Product Solutions and Statistics Services) for Windows. The research results obtained that e-money does not have a significant effect on the money supply (M1), credit cards have a negative and not significant effect on the money supply (M1), whereas debit cards have a significant positive effect on the money supply (M1).Keywords: electronic money, credit cards, debit cards, payment amounts (m1)